Assessment of river morphology based on changes in land use and land cover and the spatial and temporal variation of meandering parameters of the barak river. Issue 11 (6th October 2022) - Nath, Apurba; Ghosh, Susmita
Abstract: River morphology describes a river's cross-sectional shape, sedimentation, and erosion. The meandering parameters, oxbow formation and decadal land usage land cover (LULC) fluctuations of Barak River were investigated using 21 meandering spans to measure river morphological changes. The decadal meandering parameters were calculated reach-wise and section-wise to characterize river morphological changes. It was observed from the paired t-test that the river width significantly changed during the study period (1990–2020). Strong inter-relationships between the meandering parameters are shown from the regression analysis. The morphological investigation found a reduction in the centerline distance due to variations in the radius of curvature caused by the internal arc's reduction. As a result, the average sinuosity has decreased over time. The current work used SVM and ML techniques for LULC classification, and a comparison of ML and SVM techniques was also done. The SVM technique performs better. The decadal LULC analysis suggests that between 1990 and 2020, the areas of water bodies, forests, and bare land types declined. Whereas, agricultural and settlement areas increased. River morphology is substantially impacted by agriculture and urbanization, particularly in areas where oxbows occur simultaneously, since this work may apply to other similar meandering river management along the alluvial flood plain. HIGHLIGHTS: River morphology is affected by meandering parameters, land resource changes, and oxbow development. A minor change in meandering parameters like sinuosity, radius of curvature, etc., can affect river width, migration rate, and morphology. A statistical analysis can estimate the river's meandering parameters. Oxbow formation influence morphology. Future oxbows can be identified through morphological study, GIS technique.